Pengaruh Model Pembelajaran Contextual Teaching and Learning terhadap Literasi IPA pada Mata Pelajaran IPAS Siswa Kelas IV SDN 0401 Pasar Ujung Batu - Indah Fadliani Pasaribu; Fahrur Rozi; Robenhart Tamba; Imelda Free Unita Manurung; Lidia Simanihuruk (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This research is a quantitative research using quasi-experimental design. Before receiving treatment, the experimental group and the control group were given a pre-test to evaluate students' science literacy. The location of the research was carried out on Jalan Lintas Riau, class IV SDN 0401, Pasar Ujung Batu Village, Sosa District, Padang Lawas Regency, North Sumatra Province. The research time was carried out in the odd semester in July-October 2024/2025. The sample of this study used 25 students, namely the experimental and control classes. The data collection technique for this study used tests and interviews. Based on the results of the study, the increase in students' science literacy skills was also strengthened by empirical findings in this study, where the average post-test score in the experimental class reached 80.16, much higher than the control class which only reached 73.20. In addition, the results of the t-test showed a very small significance value (p = 0.000056), indicating that the difference in learning outcomes between the two classes was not a coincidence, but a real result of the application of the CTL model. The fact that the experimental class showed lower variance in the posttest also indicates that the CTL model is able to balance achievement between students and reduce academic gaps.